O algoritmo computacional como objeto sociotécnico: encontros da complexidade algorítmica - Aquino, Ellen Larissa de Carvalho (2020)
The algorithm is an object that passes through a timeline and precedes the formation of symbolic movements that dispute not only its practical applications, but also its interpretations. Thus, its nature has been formed by technical materialities and social dimensions, becoming a motor force that describes and transforms our present time. With a characteristic protagonism, not only because of the importance that the object has in our society, but also because of the unconscious way in which we interact daily with it, the algorithm becomes a reflection of a thought that models the construction of all socio-technical interactions. Thus, our goal is to understand the algorithm as a sociotechnical object and problematize this construction through the theoretical and practical intertwining that stem from the interactions brokered from the field of Science, Technology and Society (STS). For this to happen we propose a meeting marked by a dialogue, which gives way to the approximation of cts authors to contemporary authors who direct their studies to the artifact of the algorithm. In this sense, a dimensional and thematic approximation was proposed divided into: logic and control; automation, work and moral alienation; body, self and cyborgs; accumulation logic and economy; politics and biases; anthropology, culture and identity; rationality and intelligence.Throughout the research we adopted a triple view: The first approach describes the pseudoetimological contextualizations and the paths of dispute that pass through the history of the object. The second, approaches from hypotheses and deductions, the multidimensional construction of the object. And the third, builds a systemic modeling that approaches the existing questions in the object under the causalities of the hypotheses previously presented. Finally, we present a social imaginary, in order to resume the centrality of algorithmic discussions in view of the sociotechnical view of the object. So that we are able to constantly perform analyses on the relational complexities that describe it.